A spatial and temporal analysis of seat-belt usage and seat-belt laws - Arnab Majumdar; Robert Noland; Washington Y. Ochieng (European Regional Science Association (ERSA), 2002)
Seat-belt usage has increased significantly in the US since the introduction of mandatory seat-belt usage laws in the 1980`s. This paper analyzes the impact of these laws on increasing seat-belt usage while controlling for other state-specific variables. Spatial analyses techniques are employed to further explain these effects. Spatial autocorrelation is found in the data but diminishes over time. Spatial correlation also exhibits a clear east-west direction. Results clearly show that both secondary and primary seat-belt laws have been effective at increasing seat-belt usage. In addition, our spatial analysis suggests that these effects cross state boundaries, implying an even larger level of effectiveness than direct measurement would suggest. Despite this some unexplained spatial correlation remains.
Keywords: 330